SUBSTITUSI AGREGAT HALUS BETON MENGGUNAKAN KAPUR ALAM DAN MENGGUNAKAN PASIR LAUT PADA CAMPURAN BETON - Kandi, Yufiter Silas; Ramang, Ruslan; Cornelis, Remigildus (Jurnal Teknik Sipil, 2012)
The limited of material that occur in Sumba Barat Daya district cause the used of natural limestone and sea sand as a substitute for fine aggregate that is scientifically unknown quality, so it needs to do a study of the material. The purpose of this research is to determine the percentage of natural limestone and sea sand that can be used and to determine the quality of the resulting concrete. Specimens used in this research is concrete cylinder (diameter 15 cm and high 30 cm). The methods used for data analysis was descriptive statistics. Based on the results obtained that the percentage that can be used for sea sand is 100% and for natural limestone is 25%. The result of Quality test obtained that the concrete with natural limestone have compressive strength and split tensile strength is smaller than the normal concrete and do not reach the compressive strength of the plan. While the concrete using sea sand is concrete which produces compressive strength and split tensile strength greater than normal concrete.